Enhancing Job Performance with Self Efficacy, Innovation, and Work Behaviour at PT. Aquafarm Nusantara Tobasa - Miska Irani Tarigan; Santa Atasya Gurning (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Every organization must face several challenges when carrying out its activities. Problems that have been reported to PT. Aquafarm Nusantara Tobasa include issues with employee performance. This can happen because of the high levels of self-efficacy, innovation, and work behavior. The purpose of this research is to examine the role of self-efficacy, innovation, and performance in the workplace of PT Aquafarm Nusantara Tobasa employees. This study used a quantitative approach based on surveys and data collection through questionnaires administered to forty-five employees at PT Aquafarm Nusantara Tobasa using a sample technique known as simple random sampling. After data validity and reliability tests are run, data analysis using the augmented linear regression method with the SPSS package is initiated. This study's findings indicate that, both individually and collectively, employees' sense of self-efficacy, innovation, and work performance have a positive and statistically significant impact on their performance on the job. The coefficient of determination (R2) is 48.6%, which indicates that employees' abilities to self-efficacy, innovate, and perform their job duties can explain their performance, whereas 51.4% of the total is influenced by factors that are not included in this study. This study's limitations can be seen from the most important perspective within the company's problems.